The Impact of Workload, Workplace Spirituality, and Work Stress on The Performance of Employees of Bank Syariah Indonesia Malang Area Office - Lela Ramadhani; Siti Nurhasanah; Rizki Febriani (Universitas muhammadiyah malang, 2023)
This research aims to determine the influence of workload, workplace spirituality, and work stress on the performance of Bank Syariah Indonesia Malang Area Office employees. The number of samples of this study 80 employees. The sampling technique used in this research is saturated sample. The type of research used is survey research with a quantitative approach. The data collection technique used is a questionnaire. In this research using multiple linear regression data analysis. The research results showed that workload had a positive and significant effect on employee performance, workplace spirituality had a positive and significant effect on employee performance, and work stress had a positive and significant effect on employee performance.